30 Jahre germanistische Phraseologieforschung - Burger, Harald (HERMES - Journal of Language and Communication in Business, 2005)
In this article, a summary of some of the most important lines of phraseological research within the last 30 years is given. Although the main perspective is German, many of the problems pointed at here will be general as German contributions to this research ﬁ eld have played a most vital role within phraseological research as such. Subjects such as the “prehistory” of phraseological research, the much-discussed content of the term “phraseology”, the problem of phraseology vs. paremiology, phrasemes in texts, phraseology in dialects and national varieties, and cross-linguistic phraseology are touched upon. In concluding the article, the author regrets the fact that large parts of the English speaking world do not notice the dynamic scientiﬁ c activities undertaken in the German speaking world with respect to phraseology.